1979
DOI: 10.1111/j.1365-2842.1979.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between bruxism and temporomandibular joint dysfunction as shown by computer analysis of nocturnal tooth contact patterns

Abstract: Whilst there are many causes of temporomandibular joint dysfunction, one of the most frequently encountered is bruxism. The two conditions have many aetiological factors in common and there is a rational physiological reason why bruxism could cause temporomandibular joint dysfunction. In fact, experimental bruxism performed under laboratory conditions has been found to cause such joint dysfunction. This contention is supported by direct measurements of nocturnal tooth contact. Patients with temporomandibular j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…A study has shown that subjects with parafunctional activities occlude their teeth seven times longer than those with no such habits (38.7 min vs 5.4 min). 143 …”
Section: Biomechanics Of Tooth-implant-supported Fixed Partial Denturesmentioning
confidence: 99%
“…A study has shown that subjects with parafunctional activities occlude their teeth seven times longer than those with no such habits (38.7 min vs 5.4 min). 143 …”
Section: Biomechanics Of Tooth-implant-supported Fixed Partial Denturesmentioning
confidence: 99%
“…Finally, in human subjects who grind and clench their teeth during sleep, Trenouth (1979) found that the teeth made contact for about 5 s/min of sleep. Provided that high levels of tension are generated and that tooth clenching occurs, children might totally exhaust their jaw muscles within 15-25 min of sleep (Christensen, 1980b, d).…”
Section: Discussionmentioning
confidence: 99%
“…In a better controlled study, Trenouth (1979) compared three groups of subjects: a TMJ/bruxism group consisting of nine patients; a TMJ/non-bruxism group composed of six patients; and a non-TMJ/non-bruxisin group of ten student volunteers. The diagtiosis of TMJ dysfunction syridrotne was made on the criteria proposed by Laskin (1969) while bruxism was diagnosed on the basis of criteria proposed by Franks (1965a).…”
Section: Tmj Dysfunctionmentioning
confidence: 99%
“…Nocturnal bruxism studies should employ an operational definition consisting of rhythmical bursts of EMG activity. The use of groups similar to Trenouth's (1979) TMJ/bruxism, TMJ/non-bruxism and non-TMJ/non-bruxism groups is suggested for an adequate evaluation of nocturnal bruxism frequency and duration. The assessment of diurnal bruxism and TMJ/ MPD problems is more difficult due to the possible reactivity associated with any assessment technique.…”
Section: • • ' Ymentioning
confidence: 99%